The Use of Multimedia in PAI Learning for the Topic "Let’s Pray" Among Fourth-Grade Students at UPT SDN 14 Siguntur Muda - Junaidi (BiCED Proceeding, 2024)
Teachers play a pivotal role in determining the success of the educational process. As educators, their primary task in Islamic education is to nurture and develop students' potential in psychomotor, cognitive, and affective domains. This role involves various activities, such as teaching, motivating, habituating, and modeling. Thus, teachers are required to possess cognitive, affective, and psychomotor skills to support the achievement of educational goals. According to Muhibbin Syah, teachers also serve as designers of instruction and evaluators of student learning potential. In the context of Islamic education, these competencies are critical in creating effective learning experiences that focus on the holistic development of students.